2019
DOI: 10.1590/0034-7167-2017-0959
|View full text |Cite
|
Sign up to set email alerts
|

Nursing diagnoses in adults and elderlies in the preoperative period: a comparative study

Abstract: Objective: Analyze the nursing diagnoses of NANDA-I Taxonomy in hospitalized adults and elderlies in preoperative of general surgery and proctology. Method: cross-sectional study, exploratory, quantitative approach, developed in the general surgery ward, between March and August, 2017. Inferential statistical analysis performed using Chi-square and Fisher test, considering p-value <0.05 and 95% confidence interval. Results: Of 51 participants, 32 (62.7%) were adults and 19 (37.3%) elderlies. In adults pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
1
0
6
Order By: Relevance
“…Surgery nursing care is usually poorly documented, insufficiently represented, and inconsistently included in the patient's pathways ( Sondergaard et al, 2017 ). However, the role of nurses in identifying potential problems in patients (e.g., preoperative anxiety, postoperative acute pain, and risk for infection) is crucial for the planning and implementation of evidence-based nursing interventions based on consistent data such as NDs ( Junttila et al, 2010 ; Monteiro et al, 2019 ). In addition, studies have shown that NDs are associated with patient and organizational key outcomes, such as hospital length of stay (LOS), in mixed settings ( D'Agostino et al, 2017 ; D'Agostino et al, 2019 ); to our knowledge, little is known regarding this relationship in the surgical setting.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Surgery nursing care is usually poorly documented, insufficiently represented, and inconsistently included in the patient's pathways ( Sondergaard et al, 2017 ). However, the role of nurses in identifying potential problems in patients (e.g., preoperative anxiety, postoperative acute pain, and risk for infection) is crucial for the planning and implementation of evidence-based nursing interventions based on consistent data such as NDs ( Junttila et al, 2010 ; Monteiro et al, 2019 ). In addition, studies have shown that NDs are associated with patient and organizational key outcomes, such as hospital length of stay (LOS), in mixed settings ( D'Agostino et al, 2017 ; D'Agostino et al, 2019 ); to our knowledge, little is known regarding this relationship in the surgical setting.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Portanto, o desafio reside na complexidade da implantação e integração dos cuidados paliativos ao processo perioperatório, oportunizando-os de forma a justapor precocemente essas abordagens, com especial destaque para a enfermagem, em seu papel de protagonista, seja na dispensação de uma atenção que trabalhe na identificação de pacientes com necessidades de paliação ou no desenvolvimento de um cuidar que dispense dignidade, se paute em estratégias, ou sobretudo, seja eminentemente humano (Arnauts & Cavalheiri, 2021;Monteiro et al, 2019).…”
Section: Introductionunclassified
“…Para o enfermeiro, os cuidados paliativos incluem o manejo agressivo da dor e dos sintomas, o apoio psicológico, social e espiritual, bem como as discussões sobre planejamento avançado de cuidados, que podem incluir tomada de decisão sobre o tratamento e a coordenação de cuidados complexos (Costa & Silva, 2021). Os cuidados paliativos especializados para idosos cirúrgicos, prestados por uma equipe de enfermagem capacitada, podem ajudar a gerenciar sintomas complexos, fornece suporte adicional às famílias, resolver conflitos nos objetivos e abordagens do tratamento e auxiliar nas transições de cuidados (Monteiro et al, 2019).…”
Section: Introductionunclassified
“…Apesar de um número considerável de idosos apresentar um envelhecimento saudável e tolerar o ato cirúrgico sem intercorrências, observa-se a morbimortalidade frequente maior no idoso, se comparado ao adulto. Por outro lado, o adulto necessita de um cuidado cirúrgico eficaz e de qualidade, de modo a proporcionar retorno à rotina diária e atividades laborais (Monteiro et al, 2019).…”
Section: Introductionunclassified
“…Considerando a necessidade de oferecer uma assistência segura aos pacientes submetidos a procedimentos cirúrgicos, o posicionamento adequado garante eficiência e segurança no período perioperatório (Peixoto et al, 2019). O posicionamento cirúrgico é um trabalho de equipe, porém cabe ao enfermeiro realizá-lo, por ser um dos profissionais responsáveis pelo Bloco Cirúrgico e pelo paciente, que individualiza o cuidado com o paciente cirúrgico, permitindo uma assistência de qualidade, principalmente ao que tange a prevenção de lesões e/ou complicações no posicionamento cirúrgico (Monteiro et al, 2019).…”
Section: Introductionunclassified